2020
DOI: 10.1039/c9ta12409h
|View full text |Cite
|
Sign up to set email alerts
|

Investigating two-step MAPbI3thin film formation during spin coating by simultaneousin situabsorption and photoluminescence spectroscopy

Abstract: Here we investigate the two-step MAPbI3 thin film formation during spin coating by simultaneous in situ absorption and photoluminescence spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 44 publications
4
70
0
Order By: Relevance
“…While there are several reports on phase transformations and identification 20,21,28,60 , detailed insights into the phenomena occurring at critical synthesis and phase transition stages are desirable. Importantly, the kinetic processes occurring during nucleation and dissolution-recrystallization have not been revealed in detail so far, and are the focus of the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are several reports on phase transformations and identification 20,21,28,60 , detailed insights into the phenomena occurring at critical synthesis and phase transition stages are desirable. Importantly, the kinetic processes occurring during nucleation and dissolution-recrystallization have not been revealed in detail so far, and are the focus of the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an antisolvent, materials crystallizing out of a fluid precursor nucleate and crystallize in a broad time window, whereas the application of an orthogonal solvent is a physical route to temporally regulate supersaturation and initiate growth during material crystallization/formation. Accordingly, there are distinct differences in precursor chemistry and methods of physicochemical conversion between a one-step 9 and two-step 20,69 method which are typically discussed in the literature. The one-step method combines the organic (CH 3 NH 3 I) and inorganic precursors (PbI 2 ) in a solvent system (4:1 v:v DMF:DMSO) to afford a single colloidal precursor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it has been shown that self‐absorption effects can play an important role and need to be considered when analyzing measured PL spectra. [ 16–22 ] We recently demonstrated that self‐absorption can even lead to additional peaks in measured PL. With a relatively simple optical model it was possible to reproduce and analyze the additional peaks in the case of pure tetragonal or orthorhombic crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring film formation in-situ during different processing stage enables the assessment of parameters affecting the thin film formation during processing and hence guide process optimization. [35][36][37] Valuable insight into different perovskite deposition strategies has been obtained from in-situ monitoring techniques such as grazing incidence wide-angle X-ray scattering (GIWAXS), [38][39][40][41] optical microscopy, 6,42 and absorption measurements 21,43,44 that provided critical insight guiding process optimization towards higher quality thin films and better device performance. These experiments are often carried out in specialized experimental setups.…”
Section: Introductionmentioning
confidence: 99%